Apoiando o Diálogo por meio de Ferramentas Computacionais Móveis e Colaborativas - Diacui Medeiros Berkenbrock, Carla; Ricaldi, Tiago; Erbs da Costa, Simone (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
The Augmentative and Alternative Communication (AAC) is one of the strategies to deal with communication problems. The AAC exploits more than one communication channel for sending messages, but it not guarantee that communication will happen. This research presents aims to promote the communication and social inclusion of children with intellectual disability through the evolution of an augmentative and alternative communication system. This research also aims to support the communication of deaf people and users of Libras by means of collaborative and mobile computing tools.